Implementation of Interactive Conceptual Instruction (ICI) With Computer Simulation: Impact of Students’ Misconceptions on Momentum and Impulse Material - Kaniawati, Ida; Danawan, Agus; Suyana, Iyon; Samsudin, Achmad; Suhendi, Endi (Jurnal Ilmiah Pendidikan Fisika Al-Biruni, 2021)
Misconceptions frequently occur in various physics concepts, including momentum and impulse. Misconceptions in students must be addressed since they can hinder the learning process. This study aimed at investigating students' misconceptions on momentum and impulse material after implementing Interactive Conceptual Instruction (ICI) with computer simulations. The method employed in this study was a quasi-experimental design with One Group Pretest-Posttest Design. This research was conducted on 30 students of the tenth grade determined by the purposive sampling technique. Fifteen four-tier test items were used as the research instrument. The N-gain analysis was performed to know the reduction of misconceptions. The results showed that the N-gain value obtained was 0.46 with moderate interpretation, meaning that Interactive Conceptual Instruction (ICI) aided with computer simulations could reduce student misconceptions. The results also indicated that the misconception after treatment was smaller than before treatment. This phenomenon can be seen from the reduction of misconceptions by 11.6% after implementing Interactive Conceptual Instruction (ICI) with computer simulations. Therefore, it can be concluded that the Interactive Conceptual Instruction (ICI) with computer simulations can facilitate students in the learning process so that misconceptions can be reduced.